2020
DOI: 10.1111/jbi.13839
|View full text |Cite
|
Sign up to set email alerts
|

Speciation rate and the diversity of fishes in freshwaters and the oceans

Abstract: Aim:The number of fish taxa that occur exclusively in marine biomes is approximately equal to the number that occur in freshwater biomes. Both the geographic area and habitable volume of the marine realm are vastly greater than for Earth's freshwater ecosystems, suggesting that the density of marine species is proportionately much lower in the oceans. Because freshwater lineages are relatively recently derived from older marine lineages, this difference in species density suggests that speciation rates might b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 56 publications
3
53
0
Order By: Relevance
“…Species restricted to marine environments were coded as occurring in a seventh “marine” region. Although not our focus, these species are needed to inform the timing of colonization of freshwater regions from the marine realm (Betancur‐R et al., 2012, 2015; Rabosky, 2020). Our model was time‐stratified to apply constraints on dispersal in accordance with changing connectivity of continents.…”
Section: Methodsmentioning
confidence: 99%
“…Species restricted to marine environments were coded as occurring in a seventh “marine” region. Although not our focus, these species are needed to inform the timing of colonization of freshwater regions from the marine realm (Betancur‐R et al., 2012, 2015; Rabosky, 2020). Our model was time‐stratified to apply constraints on dispersal in accordance with changing connectivity of continents.…”
Section: Methodsmentioning
confidence: 99%
“…While BAMM has been criticized in the literature (Moore et al, 2016), Rabosky et al, (2017) have argued that previous criticisms about BAMM are incorrect or unjustified, although it is true that the method, like many others in the same family of models, is not exactly correct (Laudanno et al 2020). More importantly, over the last few years, several studies have demonstrated that most inferences seem to be robust when estimating diversification in distinct groups of animals (Rabosky et al 2013; Shi and Rabosky 2015; Chang et al 2019; Rabosky 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In light of the present study, it is possible that faster freshwater rates inferred by past studies were actually driven by lacustrine species, and not reflective of a general difference between marine and freshwater biomes. Indeed, Rabosky (2020) found that apparently faster average freshwater rates of speciation in actinopterygians were driven by select clades and were not broadly characteristic of marine-to-freshwater transitions. Lacustrine cichlids in particular have the fastest speciation rates among all fishes (Burress and Tan 2017; McGee et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Note that higher turnover in freshwater compared to marine habitats cannot explain the freshwater paradox, because species richness will not change when speciation and extinction rates are about equal (see also Meseguer and Condamine 2020). Studies including all ray-finned fishes have found no difference in diversification rates (Carrete Vega and Wiens 2012), faster rates in marine habitats (Betancur-R et al 2015), faster rates in freshwater (Tedesco et al 2017a), or faster rates in only some freshwater clades (Rabosky 2020). The only study to my knowledge that exclusively used the fossil record to test this hypothesis found that the accumulation of family diversity has slowed over time in marine but not freshwater fishes (Guinot and Cavin 2015).…”
Section: Introductionmentioning
confidence: 99%